Occurrence of psychiatric disorders in the patients of multi drug resistant tuberculosis under treatment - Kumar, Anand; Chaudhari, Dhananjay; Anand, Rahul; Verma, Sanjay Kumar; Kumar, Avdhesh; Chaudhri, Sudhir (International Journal of Research in Medical Sciences, 2018)
Background: Tuberculosis (TB) is considered as one of the leading causes of mortality worldwide. Even though fatality of TB is well known, treatment non-adherence is major barrier related to management of TB. Studies have shown that there is strong association between psychiatric disorders and treatment nonadherence to TB. Psychiatric issues present a challenge in the treatment of patients with multi drug-resistant tuberculosis (MDR-TB). Both baseline psychiatric disorders and development of psychiatric complications related to anti-tuberculosis drugs require aggressive management for better management of TB. The objective of the present endeavour was to study the occurrence of psychiatric complications in patients of MDR-TB during treatment Methods: Patients of MDR-TB registered at PMDT centre situated at a tertiary level hospital were screened for psychiatric disorder by using GHQ-12 and assessment was done using structured clinical interview for DSM-IV-TR (SCID-1) research version. Diagnosis of psychiatric disorder was made on the basis of DSM-IV-TR. Results: Psychiatric disorders were already present in 8 (6.15%) patients before the start of MDR-TB treatment and development of psychiatric disorder in 12 (9.23%) patients after initiation of the treatment. Depressive disorder (n=9; 6.9%), anxiety disorder (n=5; 3.8%) and psychosis (n=4; 3.1%) were most frequent psychiatric disorders. Conclusions: GHQ-12 was found to be very useful screening instrument for detection of psychiatric disorders. The regimen IV anti tubercular drugs used for the treatment of MDR-TB drug resistant tuberculosis, significantly increases the risk of development of psychiatric disorders.